Novel assessment of intestinal anastomotic perfusion using ICG SPY in a continuous flow LVAD patient. Issue 11 (12th November 2020) - Kaufman, Daniel; Sherwinter, Danny; Kaleya, Ron; Saunders, Paul C
Abstract: HeartMate II left ventricular assist device (LVAD) assists heart failure patients by generating continuous flow via axial flow pump placed in the left ventricle. Little is known of the effect of continuous flow on intestinal anastomoses. This is the first case visually documenting altered perfusion patterns in patients with LVADs using indocyanine green (ICG). A 72-year-old male required a colon resection, for adenocarcinoma, following implantation of an LVAD. Perfusion of the anastomosis was evaluated using indocyanine. During the assessment, an unusual perfusion pattern was noticed. Normally, flow as measured by SPY is seen as an initial blush of contrast followed by a gradual, pulsatile increase in the progression of the indocyanine through the tissues. In this patient, instead of the usual initial blush, a continuous beam of ICG was seen to flow though the blood vessels. This novel perfusion pattern is consistent with flow generated from LVAD.